Mitochondria and the hallmarks of cancer. (25th December 2015) - Giampazolias, Evangelos; Tait, Stephen W.G.
Abstract : Mitochondria have traditionally been viewed as the powerhouse of the cell, where they serve, amongst other functions, as a major source of ATP generation. More recently, mitochondria have also been shown to have active roles in a variety of other processes, including apoptotic cell death and inflammation. Here we review the various ways in which mitochondrial functions affect cancer. Although there are many diverse types of cancer, hallmarks have been defined that are applicable to most cancer types. We provide an overview of how mitochondrial functions affect some of these hallmarks, which include evasion of cell death, de‐regulated bioenergetics, genome instability, tumour‐promoting inflammation and metastasis. In addition to discussing the underlying mitochondrial roles in each of these processes, we also highlight the considerable potential of targeting mitochondrial functions to improve cancer treatment. Abstract : While cancer is a diverse disease, various hallmarks have been defined that are shared by most cancer types. Mitochondria play key roles in many of these hallmarks, controlling diverse processes that include cellular energetics, cell death and inflammation. In this review we discuss how mitochondria regulate these events and highlight how they can be targeted to improve cancer treatment.